Dietary insulin index and load in relation to the risk of diminished ovarian reserve: a case–control study - Ghavami, Abed; Mehrabani, Sanaz; Khodarahmi, Mahdieh; Mokari-Yamchi, Amin; Vajdi, Mahdi; Ghasemi-Tehrani, Hatav; Askari, Gholamreza (Frontiers in Nutrition, 2025)
BackgroundDiminished ovarian reserve (DOR) occurs as a result of a decrease in the quantity and quality of oocytes, which can negatively affect fertility. Diet is one of the modifiable factors that plays an important role in preventing or exacerbating numerous diseases. As the effects of diet on the risk of DOR were not well-defined, this study was designed to investigate the association between DOR and dietary insulin index (DII) and dietary insulin load (DIL).Materials and methodsA total of 370 Iranian women participated in this case–control study: 120 individuals with DOR and 250 control subjects matched for age and body mass index. A validated semiquantitative 80-item food frequency questionnaire was used to assess the DII and DIL. Serum anti-Müllerian hormone levels were measured, the number of antral follicles was counted, and various anthropometric indices were evaluated. In addition, the relationship between the DII and DIL, and the risk of DOR was analyzed using multivariable logistic regression.ResultsThe unadjusted model of analysis found no significant relationship between the risk of developing DOR, and the DII and DIL. However, the findings showed that women who were in the highest quartile of the DII had a 1.29 times higher chance of having DOR (odds ratio: 1.29; 95% confidence interval: 1.07 to 3.93) when factors such as energy consumption and physical activity were considered. Furthermore, participants in the third and fourth quartiles of the DII and DIL had significantly higher odds of developing DOR when all possible confounders were taken into account.ConclusionThe risk of DOR increased with an increase in the DII and DIL. However, further clinical trials and prospective cohort studies are needed to support this finding.